Bitka na Neretvi - Bulajić, Veljko (Yugoslavia : Kinema ; Udruženi jugoslovenski producenti ; Igor Film Rome ; Eichberg Film, 1969)
This Hollywood style war-flick is based on the historic German offensive against the Yugoslav partisans in 1943 in Western Bosnia. The film’s international reputation is mostly due to its enormous budget and the fleet of international film stars who played major roles, including Yul Brynner, Sergei Bondarchuck, Orson Welles, Hardy Krüger and Franco Nero. The film tells several interwoven stories stressing the importance of comradeship in wartime with obvious pro-communist leanings. Cornered by the overwhelming joint German, Italian and Chetnik forces, Yugoslav partisans together with 4500 wounded find themselves surrounded near the Neretva river. The only way out is by the bridge over the river, but with heavy enemy forces waiting on the other side, partisan headquarter decide on a strategic trick – to destroy the bridge. Predicting that the partisans will attempt a suicidal sortie, the surprised joint Axis forces transfer their forces to the other side of the river, not knowing that, during the night, the partisans will build a temporary bridge near the destroyed one and cross to the other side, thus outsmarting the enemy. In the epic final scene several of the main characters are killed and thousand of innocent people lose their lives.
Keywords: Fiction films